Framing the migrant subject : Shane Maloney's Stiff - L. Di Pietro (Law Text Culture, 1995)
How do you get to be the kind of victor who can claim to be the vanquished also ? Jamaica Kincaid I wish to problematise the representations of non-Anglo migrants in the crime thriller Stiff, written by Shane Maloney, regular humour columnist for the magazine Arena. The author structures the meanings conferred to non-Anglo migrants and Australianness by using irony and the crime thriller genre itself. The technique of irony which characterises the novel is a mechanism which enables the author to get away with untenable positions by 'progressive' standards. This ironic tone reverses relations of power casting the narrator Murray Whelan in the role of victim: the failed husband, the precarious father, the sexually inept man and the Anglo male bureaucrat/activist who has to deal with 'foreigners'. Whelan, electorate officer for the ALP is the socially engaged man simultaneously assailed by feminism and multiculturalism. He is at once the victor and the vanquished.